Carotid Doppler findings among patients admitted with stroke in two tertiary care facilities in Uganda - Walubembe, Jonathan; Ssinabulya, Isaac; Mubuuke, Aloysius G.; Kagwa, Mark Mohan; Babirye, Deborah; Okot, Jerom; Bongomin, Felix; Nakku, Miriam; Okello Ongom, Diana; Ameda, Faith (Research Square, 2023)
Carotid Atherosclerotic Disease (CAD) Doppler ndings including carotid artery stenosis, thickened intima media thickness, and high-risk atherosclerotic plaques are associated with increased risk of stroke and symptomatic cerebrovascular disease. However, few studies have explored these Doppler characteristics among stroke patients in Africa. This study, therefore, investigates these carotid artery Doppler characteristics among stroke patients in Uganda. Methods A hospital-based cross-sectional study of 95 stroke patients attending two national referral hospitals in Uganda between March and July 2022. Following the caption of their sociodemographic and clinical characteristics, they underwent Doppler sonography of the extracranial carotid arteries using a standard carotid Doppler protocol. Multivariate logistic regression was used to determine factors associated with abnormal carotid Doppler parameters (i.e., carotid intima-media thickness, carotid stenosis). Results The mean age of the study participants was 61 ± 13 years with 60% (57/95) of the participants being male. Most participants had an ischemic stroke (67%), hypertension (76.4%), and used alcohol (58.9%). The prevalence of signi cant carotid stenosis in participants with ischemic stroke was 12.5% (8/64) (i.e., 7.8% had severe carotid stenosis and 4.7% had moderate stenosis). The prevalence of high carotid intima media thickness (CIMT) and atherosclerotic plaques were 31.6% (30/95) and 26.3% (25/95), respectively. Most atherosclerotic plaques were echogenic. Age above 60 years (adjusted odds ratio [aOR] = 5.2, 95% Con dence Interval [CI]:1.97-14; p < 0.010), high low-density lipoprotein cholesterol (aOR = 4.2, 95% CI: 1.29–8.79; p = 0.013) increased the likelihood of having abnormal CIMT. Conclusion The burden of carotid atherosclerotic disease is increasing among stroke patients in Uganda. Large-scale epidemiological studies are needed to further pro le the disease in high risk populations.
: a Hospital-based Cross-sectional Study